Pemberdayaan Ekonomi Masyarakat Berbasis Ekowisata - Rini Setiawati, Rini Setiawati Rini Setiawati (BINA' AL-UMMAH, 2017)
Rural areas have abundant resource potential, there is an optimal use of natural and human resources in the Village. One of the efforts to utilize the optimal local resources is to develop tourism with the concept of ecotourism. In this context tourism has an integral part of conservation efforts, local economic empowerment and promotes greater respect for cultural or cultural differences. Gunung Rejo Village is a tourist village by developing ecotourism with environmental conservation with the aim to achieve sustainability either economic community or natural potential.This research is field research with qualitative approach. The research data is explored in depth through interview technique, observation and documentation about the profile of community economic empowerment in ecotourism program in Gunung Rejo Village. Sources of research data were selected using non random sampling based on certain criteria. The problem in this research is how ecotourism development activity and how economic empowerment of ecotourism based society in Gunung Rejo Village, Way Ratai Sub District, Pesawaran Regency.Data collection is done by three ways, namely interview conducted by the researcher is a structured interview by preparing a list of questions, Observations conducted by researchers is non-participant observation. Documentation conducted by researchers to dig information as supporting research findings conducted in the form of interviews and observation. Data analysis used is an interactive analysis model that includes data reduction, data presentation, and conclusion.The results of this study indicate that the development activities partnerships with the community, Provide understanding to the community about the procedures for managing the tour and utilize natural resources and human and cultural resources, Building community capacity building in developing and improving productivity results of household business, Preparing the development and provision of tourism service facilities. Economic empowerment of the community through increased access through hamlet activities, capacity building through training, and improvement of business community productivity through home business training activitiesKata Kunci : Pemberdayaan Ekonomi Masyarakat, Ekowisata